The Role of Principal Leadership Style in Improving the Performance of Public and Private Elementary School Teachers in Bandung Regency - Rizqi, Faturahman; Hadi, Muhammad Sofian; Surizkika, Aldi (Journal of English Language and Education, 2026)
The performance of elementary school teachers is the foundation of learning quality, but various competency improvement programs are often not optimal because performance issues are also influenced by organizational factors at the school level. The literature still shows a gap in explaining how school principal leadership works through daily "work channels" such as communication and collaboration, especially when comparing public and private elementary schools. This study aims to analyze the role of principal leadership styles in improving the performance of public and private elementary school teachers in Bandung Regency. The study uses a qualitative approach with semi-structured interviews with principals and teachers, analyzed through thematic coding and cross-school source triangulation. The results show that leadership patterns tend to be combinative, with democratic practices dominating in the aspect of communication, which is most strongly related to increased collaboration and consistency in teacher work, while authoritarian practices emerge in certain situations for control purposes. It is concluded that strengthening communication and collaboration are key leadership mechanisms for improving teacher performance.